Effect of the difference in applied potentials on the structural features of CoCdSe thin films - Omarova, A.; Kozlovskiy, A.L.; Kenzhina, I.E.; Kadyrzhanov, K.K.; Kanyukov, E.Yu. (Recent Contributions to Physics, 2020)
One of the promising materials in the field of semiconductors today is structures based on cadmium, selenium, tellurium and their compounds having one structural type AIIBVI, the interest in which is due to the possibility of their use in various photoelectronic devices, solar cells, LEDs, catalysts, etc. This work is devoted to the study of the properties of thin films based on CoCdSe. As a synthesis method, the electrochemical deposition method was used, which allows us to obtain thin films with specified parameters with high accuracy. Results of the effect of the applied potentials difference on the structural features of CoCdSe thin films are obtained. As substrates for producing thin films, polyethylene terephthalate polymer films were used, which have good adhesion properties, which make it possible to obtain thin films uniform in height and composition. It has been established that a change in the difference in applied potentials leads not only to a change in the thickness of thin films for a given synthesis time interval, but also to a change in the stoichiometric and phase composition of thin films. Using the method of X-ray phase composition, it was found that an increase in the applied potentials difference leads to an increase in the CoSe phase, as well as structural ordering and a decrease in the dislocation density of defects in the films.